THE RELATIONSHIP BETWEEN THE TDABC APPROACH AND TARGET COSTS AND ITS ROLE IN REDUCING COSTS AND INCREASING THE COMPETITIVENESS OF COMPANIES - M. Imad Nayef Turki; M. Abdullah Hussein Jameel; A.M. Bassem Rashid Ali (Scholars Digest Publishing, 2025)
The research aimed to demonstrate the relationship between the time-driven activity-based costing (TDABC) approach and the target costing approach, and their combined role in reducing costs and increasing corporate competitiveness. This is particularly true in light of the challenges facing economic units in Iraq due to high costs and the ineffectiveness of traditional costing systems. The research relied on an analysis of the role of each approach in addressing the shortcomings of the traditional system. TDABC provides greater accuracy in allocating indirect costs by using time as a primary cost driver, while the target costing approach contributes to strategic planning to reduce costs by determining the target price and planned profit. The research concluded that combining these two approaches provides an effective integrative framework for cost management, supporting the ability to make accurate decisions that contribute to improving financial and operational performance and achieving a competitive advantage in the market. The results also revealed a gap in studies and actual applications of this integration within the Iraqi context, reflecting the need for future applied studies to support the adoption of this advanced accounting approach.
Keywords: Time-Driven Costing (TDABC), Target Costing, Cost Reduction, Competitiveness, Management Accounting.